2021
DOI: 10.1371/journal.pone.0251946
|View full text |Cite
|
Sign up to set email alerts
|

Value of quantitative analysis in lung computed tomography in patients severely ill with COVID-19

Abstract: Introduction Quantitative computed tomography (QCT) is used to objectively assess the degree of parenchymal impairment in COVID-19 pneumonia. Materials and methods Retrospective study on 61 COVID-19 patients (severe and non-severe; 33 men, age 63+/-15 years) who underwent a CT scan due to tachypnea, dyspnoea or desaturation. QCT was performed using VCAR software. Patients’ clinical data was collected, including laboratory results and oxygenation support. The optimal cut-off point for CT parameters for predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Except age and comorbidities independently associated with higher risk of poor outcomes there are multiple biomarkers and results of image tests [29][30][31]. In our research, a significant association between death and ineffectiveness of HFNO was observed with respect to the values of CRP, procalcitonin, ferritin, D-dimers, creatinine, LDH and lymphocytes as well as intensification of changes in CT scans.…”
Section: Discussionsupporting
confidence: 48%
“…Except age and comorbidities independently associated with higher risk of poor outcomes there are multiple biomarkers and results of image tests [29][30][31]. In our research, a significant association between death and ineffectiveness of HFNO was observed with respect to the values of CRP, procalcitonin, ferritin, D-dimers, creatinine, LDH and lymphocytes as well as intensification of changes in CT scans.…”
Section: Discussionsupporting
confidence: 48%
“…The rapidly increasing GGOs may be associated with early-stage symptoms. Rorat M et al retrospectively analyzed 61 patients with COVID-19 who underwent a CT scan due to suspicious symptoms of pneumonia during deterioration of health [23]. Quantitative CT was performed using deep learning and revealed a significantly higher severity of changes in type of GGOs and consolidation in patients with severe disease than in those with nonsevere disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are several papers that suggest the usefulness of CT evaluation using deep learning of COVID-19, but each has different end points and analysis methods [24,25]. Additionally, most of the studies focus on detection and diagnosis, and those that consider severity and prognosis are relatively rare [23]. The advantages of our method are as follows: 1.…”
Section: Discussionmentioning
confidence: 99%
“…Total lesion calculation was also performed, which made a total of ground-glass opacity and consolidation volumes [ 17 ]. The Thoracic VCAR is already in clinical practice in Chest CT affected by COVID-19 infections [ 17 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%